Light quality in vitro growth and acclimatization of two varieties of Phalaenopsis amabilis alba Blume (Orchidaceae) - Massaro, Raquel; Fadin, Dauri Aparecido; Moraes, Cristiano Pedroso de; Vieira, Antônio Sanches; Marteline, Marco Aurélio (Iheringia, Série Botânica., 2018)
This study aimed to analyze the in vitro growth and acclimatization of two cultivars (cv. 6323 and cv. 6546) of the species under different light quality regimes. To evaluate the influence of light quality on the growth of seedlings of the two cultivars, plants were submitted to five different light treatments: white, blue, yellow, green and red obtained by wrapping vials with colored cellophane sheets. After 60 days of cultivation, the multivariate statistical evaluation of the results was performed. From the biometric data analysis, it could be seen that the in vitro and ex vitro growth of P. amabilis were influenced by different light qualities and the resulting variation occurs due to the influence of the genotype. The blue spectrum exerted a greater influence on the cv. 6323 and the green spectrum on the cv. 6546.